Probabilistic cost estimation methods for treatment of water extracted during CO2 storage and EOR. (October 2015) - Sullivan Graham, Enid J.; Chu, Shaoping; Pawar, Rajesh J.
Graphical abstract: Contributions of different treatment factors to cost variance in the Madison Formation and for seawater cases, for a produced water case. Madison Fm. (Generic mineral scaling calculations; 14, 000 mg/L TDS); Madison Fm. with detailed mineral scale calculations (14, 000 mg/L TDS); and seawater (35, 000 mg/L TDS) cases. Highlights: The WTM provides accurate energy costs for Wyoming and seawater CCUS examples. Organic pretreatment is a significant contributor to EOR treatment costs. Truck transport is a high-cost component but contributes little to cost variance. Feed temperature and storage costs are significant contributors to cost variance. Abstract: Extraction and treatment of in situ water can minimize risk for large-scale CO2 injection in saline aquifers during carbon capture, utilization, and storage (CCUS), and for enhanced oil recovery (EOR). Additionally, treatment and reuse of oil and gas produced waters for hydraulic fracturing will conserve scarce fresh-water resources. Each treatment step, including transportation and waste disposal, generates economic and engineering challenges and risks; these steps should be factored into a comprehensive assessment. We expand the water treatment model (WTM) coupled within the sequestration system model CO2 -PENS and use chemistry data from seawater and proposed injection sites in Wyoming, to demonstrate the relative importance of different water types on costs, including little-studied effects of organic pretreatment and transportation. We compare the WTM with an engineering water treatment model, utilizing energy costs and transportation costs. Specific energy costs for treatment of Madison Formation brackish and saline base cases and for seawater compared closely between the two models, with moderate differences for scenarios incorporating energy recovery. Transportation costs corresponded for all but low flow scenarios (<5000 m 3 /d). Some processes that have high costs (e.g., truck transportation) do not contribute the most variance to overall costs. Other factors, including feed-water temperature and water storage costs, are more significant contributors to variance. These results imply that the WTM can provide good estimates of treatment and related process costs (AACEI equivalent level 5, concept screening, or level 4, study or feasibility), and the complex relationships between processes when extracted waters are evaluated for use during CCUS and EOR site development.